Living Wing Sdn. Bhd. / Alia Batrisyia Azman - Azman, Alia Batrisyia (2022)
This study is an effort to figure out how the ideas can be fully implemented. Everyone at UiTM Arau who register Fundamentals of Technology Entrepreneurship (ENT600) are required to complete a case study project as part of their studies. As a result, we had the opportunity to research a company that produced the same product that we want to develop for this purpose. The selected company in this case study is BROS that produce various types of bottles. In this case study, we used SWOT analysis to examine the company's strengths, weakness, opportunities, and threats in the real world. The company's general information was gathered in the first section of the project report.